Phenotypic Mapping of Animal Genetic Resources in Dehradun District of Uttarakhand - Kumar, Amod; Mishra, Anil Kumar; Arora, Reena; Kumar, Avnish; Singh, AK; Shahi, Bijendra (Journal of Livestock Biodiversity, 2025)
Phenotypic mapping refers to the systematic documentation of livestock and poultry populations within specific geographical regions. This approach aids in cataloguing all recognized breeds and populations present in the area, as well as monitoring populations that migrate over time due to their functional value or economic viability. A field survey was conducted in five blocks of Dehradun district and nearby area (Sahaspur, Vikasnagar, Doiwala, Kalsi, and Jwalapur) to document livestock composition and identify distinct populations. The survey revealed predominance of Jersey × Holstein Friesian crossbreds, along with the presence of Belahi cattle, Murrah and Gojri buffaloes, non-descript goats, and backyard poultry including Aseel and Kadaknath breeds. Notably, a lesser known cattle population was identified in the Kalsi and Chakrata blocks, Chakrati or Kalsi cattle. These animals exhibited distinct traits including small body size, white to light grey coat colour, and prominent hump and dewlap. The identification of this population underscores the need for further phenotypic and genetic studies, and conservation strategies to safeguard livestock biodiversity in the Himalayan region. This study has established the comprehensive information about the livestock and poultry populations in the Dehradun district of Uttarakhand.